The activities of purine catabolizing enzymes in plasma and bronchial washing fluid in patients with lung cancer and pneumonia - Akyol, O; Gökbulut, I; Köksal, N; Akin, H; Özyurt, H; Yildirim, Z (Pergamon-Elsevier Science Ltd, 2001)
[Abstract Not Available]
Keywords: Obstructive Pulmonary-Disease; Serum Adenosine-Deaminase; Bronchoalveolar Lavage Fluid; Xanthine-Oxidase Activity; Superoxide-Dismutase